2016
DOI: 10.1038/npjgenmed.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Inherited breast cancer predisposition in Asians: multigene panel testing outcomes from Singapore

Abstract: Genetic testing for germline mutations in breast cancer predisposition genes can potentially identify individuals at a high risk of developing breast and/or ovarian cancer. There is a paucity of such mutational information for Asians. Panel testing of 25 cancer susceptibility genes and BRCA1/2 deletion/duplication analysis was performed for 220 Asian breast cancer patients or their family members referred for genetics risk assessment. All 220 participants had at least one high-risk feature: having a family his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 39 publications
6
32
2
Order By: Relevance
“…The other half of patients who received genetic testing was subsidised. The uptake rates of the subsidised groups are higher than that of those who did not receive subsidies (table 3), which indicates that cost is, in general, a barrier to patients with financial difficulties 29…”
Section: Discussionmentioning
confidence: 94%
“…The other half of patients who received genetic testing was subsidised. The uptake rates of the subsidised groups are higher than that of those who did not receive subsidies (table 3), which indicates that cost is, in general, a barrier to patients with financial difficulties 29…”
Section: Discussionmentioning
confidence: 94%
“…A study within the Dutch population reported CS as occurring in approximately one in 250,000 individuals (Nelen et al., ); however, at the time CS was the only clinical diagnosis associated with PTEN, thus this study did not include individuals with other PHTS phenotypes and is likely an underestimate of true disease prevalence, which is to date unknown. PTEN pathogenic variants have been identified in 1% or fewer of unselected individuals with breast, thyroid, or endometrial cancers, and higher rates (up to 17% in one study) among patients with autism and macrocephaly (Butler et al., ; Nagy et al., ; Ring et al., ; Tung et al., ; Wong et al., ). To consider the maximum possible frequency of PHTS in the population, the group considered the population incidence and percent causation owed to PHTS for these four PHTS‐component features ().…”
Section: Resultsmentioning
confidence: 99%
“…In 37 multigene panel studies reviewed, the overall frequency of TP53 carriers identified ranged from 0% to 4.4%, and was variable between patient groups according to ancestry or previous BRCA testing (). This frequency was highest in reports from Asia and the Middle East, although this may reflect differences in patient referral patterns (Wong et al., ). Despite high uptake of panel testing in the USA (Robson, ), debate about the clinical utility of all genes included in cancer panels, and the high detection rate of variants of unknown significance (van Marcke, De Leener, Berliere, Vikkula, & Duhoux, ) has delayed routine use of multigene panel testing in clinics worldwide.…”
Section: Discussionmentioning
confidence: 95%
“…While most of the published multigene panel studies tested patients of (mostly) European ancestry, a limited number of studies have analyzed other populations. We therefore compared the frequency of TP53 carriers among cohorts of patients with different ancestries and without previous BRCA1/2 testing (BRCA unknown) for Europeans (Bunnell et al., ; Buys et al., ; Castera et al., ; Couch et al., ; Couch et al., ; Doherty, Bonadies, & Matloff, ; Eliade et al., ; Kapoor et al., ; Kraus et al., ; Moran et al., ; Pinto et al., ; Rummel, Lovejoy, Shriver, & Ellsworth, ; Schroeder et al., ; Shirts et al., ; Susswein et al., ; Tedaldi et al., ; Tung et al., ; Tung et al., ) Asians (Kwong et al., ; Lin et al., ; Ng et al., ; Rajkumar, Meenakumari, Mani, Sridevi, & Sundersingh, ; Wong et al., ; Yang et al., ), and Middle Easterns (Jalkh et al., ; Lolas Hamameh et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation